2021
DOI: 10.1186/s12939-021-01479-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring different methods to evaluate the impact of basic income interventions: a systematic review

Abstract: Background Persistent income inequality, the increase in precarious employment, the inadequacy of many welfare systems, and economic impact of the COVID-19 pandemic have increased interest in Basic Income (BI) interventions. Ensuring that social interventions, such as BI, are evaluated appropriately is key to ensuring their overall effectiveness. This systematic review therefore aims to report on available methods and domains of assessment, which have been used to evaluate BI interventions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…This review will focus on studies that investigate GBI programs and initiatives implemented in developed high‐income countries. The search strategy proposed for this review builds on those used in previous reviews on GBI (Gibson, 2020; Pinto, 2021). Searches using both keywords and database‐specific controlled vocabulary will be conducted in relevant databases, and complementary searches will be done to identify additional studies as well as pertinent gray literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review will focus on studies that investigate GBI programs and initiatives implemented in developed high‐income countries. The search strategy proposed for this review builds on those used in previous reviews on GBI (Gibson, 2020; Pinto, 2021). Searches using both keywords and database‐specific controlled vocabulary will be conducted in relevant databases, and complementary searches will be done to identify additional studies as well as pertinent gray literature.…”
Section: Methodsmentioning
confidence: 99%
“…Effects on poverty were assessed using two measures which are based on income alone: the poverty headcount and the squared poverty gap. Gibson et al (Gibson, 2020) conducted a scoping review of interventions similar to basic income in upper‐middle‐income and high‐income countries, which examined health outcomes. One qualitative study was included that reported increased food security. Günther (Günther, 2020) reviewed 60 articles as part of a Master's thesis on basic income schemes and experiments globally to evaluate income and employment elasticities. Gupta et al (Gupta, 2021) conducted a review of basic income experiments globally and examined the effect of mitigating income poverty on mental health. Pinto et al (Pinto, 2021) conducted a systematic review that identified 86 articles on 10 basic income interventions implemented globally to examine the various methods used to evaluate the effectiveness of the interventions. Yang et al (Yang, 2021) reviewed 152 pieces of literature on basic income theories and empirical cases (15 studies globally) to analyze the relationship between conceptual definitions of basic income and how interventions have been implemented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of the effect of these emergency financial schemes, targeting both individuals and enterprises, on quality of life, mental health, and suicide prevention was also discussed in Japanese studies, as a possible important mitigating factor ( Ikeda et al, 2021 ; Tanaka & Okamoto, 2021 ). In consideration of mid- and long-term socioeconomic consequences of the pandemic, such financial and social support schemes beyond short-term emergency schemes should be strengthened widely, as these measures are recommended and shown to be effective ( Hensher, 2020 ; Pinto et al, 2021 ; Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While historically much evaluative research on UBI has tended to focus on its potential impacts on workforce participation, over the last 2 decades there has been a shift to include a broader range of outcomes, including health [ 22 ]. Two recent reviews of interventions similar to UBI suggest they may be beneficial for mental health and well-being [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%